The epidemiologic status of animal bite and the effect of wasting stray dogs on the incidence of animal bites in Galikesh County since 2009 until 2013 - Ali Maleka (Jorjani Biomedicine Journal, 2018)
Background & Objective: Animal bites are a major threat to human health, while the subsequent infections such as Rabies could be lethal. The aim of this study was to determine the epidemiologic status of animal bite and the effect of wasting stray dogs on the incidence of animal bites in Galikesh County since 2009 until 2013. Methods: The present study was a cross-sectional study with descriptive-analytical approach. A total of 1712 animal-bitten cases who were residing in Galikesh during the years of 2009-2013 were enrolled by census method. Data were collected from the recorded documents of animal-bitten individuals and analyzed by SPSS. Results: Of all cases, 1203 (70.3%) individuals were male and 509 (29.7%) were female. Regarding the age, cases were ranged between 1 to 89 years with a mean and standard deviation of 26.88 ± 18.39 years. The majority of bite cases (92.3%) were related to dogs. Moreover, 71.4% of bites were on legs. There was a significant relationship between sex and the place of residence as well as between the place of the event (biting) and delay to the first vaccination (P <0.05). Wasting the stray dogs has no effect on reducing the incidence of bites (P <0.05). Conclusion: The current plan of wasting the stray dogs has no effect on reducing the incidence of bites in Galikesh. Therefore, it is recommended to carry out controlling programs, education and community awareness in this field.